Твір Ібн Фадлана у дослідженнях А. П. Ковалівського - Мітряєв, А.І. (Хазарский альманах, 2015)
Стаття, заснована на архівних матеріалах, описує трагічне життя та наукову діяльність Андрія Ковалівського (1895–1969), українського арабіста, який підготував перше видання книги подорожі до волзьких булгар Ібн Фадлана у 921–922 рр., опублікованої в 1939 р. В статье на основе архивных материалов описывается трагическая жизнь и научная деятельность Андрея Ковалевского (1895–1969), украинского арабиста, подготовившего первое издание книги о путешествии к волжским булгарам в 921–922 годах Ибн Фадлана, изданной в 1939 г. The article, based on archive material, describes the tragic life and scholarly activity of Andrij Kovalivskij (1895–1969), the Ukrainian Arabist who prepared the first edition of Ibn Fadlan’s book of travel to Volga Bulgars in 921–922 published in 1939 (because at the time he was victimized by the Stalinist purges and imprisoned, this edition had to be published as “edited by I. Ju. Krachkovskyj”, in the same year Zeki Velidi Togan published Ibn Fadlan’s account with an excellent historical commentary, it is recognized that Kovalivskij’s edition is much stronger from the philological point of view, while Togan’s edition is superior from the point of view of historical commentary, in 1956 he published an expanded version of his first edition-note from the editors).